An Empirical Analysis of the Impact of Government Health Expenditures on the Performance of the Health Sector in Nigeria - Danladi, Gwaison Panan (Innovation Journal of Social Sciences and Economic Review, 2021)
The purpose of this study is to investigate the impact of government health expenditures on the performance of the health sector in Nigeria over the period from 1979 to 2019. The study employs an ex-post facto research design and utilizes annual time series data obtained from the World Development Indicators (WDI) and the Central Bank of Nigeria (CBN) Statistical Bulletin. To analyze the data, the dynamic ordinary least square (DOLS) estimation method is used, allowing for the assessment of the relationship between government spending on health and sector performance, as proxied by life expectancy. The findings reveal that both capital and recurrent health expenditures are positively associated with improvements in life expectancy. However, while recurrent health expenditures are statistically insignificant, capital health expenditures show a significant and positive impact on life expectancy. The study concludes that effective allocation and utilization of capital health expenditures can significantly enhance health sector performance in Nigeria. The implications suggest that policymakers should prioritize capital investments in health infrastructure, such as the construction and equipping of health centers, to improve accessibility and overall health outcomes. Future research could explore the long-term effects of different types of health expenditures on other health indicators and economic growth.
Keywords: Health Capital Expenditures; Health Recurrent Expenditures; Life Expectancy; Dynamic Ordinary; Least Square; COVID-19.